2019
DOI: 10.1002/bip.23319
|View full text |Cite
|
Sign up to set email alerts
|

Sequence characteristics responsible for protein‐protein interactions in the intrinsically disordered regions of caseins, amelogenins, and small heat‐shock proteins

Abstract: Milk caseins and dental amelogenins are intrinsically disordered proteins (IDPs) that associate with themselves and others. Paradoxically, they are also described as hydrophobic proteins, which is difficult to reconcile with a solvent‐exposed conformation. We attempt to resolve this paradox. We show that caseins and amelogenins are not hydrophobic proteins but they are more hydrophobic than most IDPs. Remarkably, uncharged residues from different regions of these mature proteins have a nearly constant average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 107 publications
(242 reference statements)
2
32
0
Order By: Relevance
“…In general, molecular chaperones are classified into two classes, namely stabilising 'holdases' [40] and energy dependant 'foldases'. In agreement with previous studies [21][22][23][24]41,42], our data are consistent with β-CN functioning as a holdase to prevent protein aggregation without refolding aggregation-prone proteins to their native state.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In general, molecular chaperones are classified into two classes, namely stabilising 'holdases' [40] and energy dependant 'foldases'. In agreement with previous studies [21][22][23][24]41,42], our data are consistent with β-CN functioning as a holdase to prevent protein aggregation without refolding aggregation-prone proteins to their native state.…”
Section: Discussionsupporting
confidence: 93%
“…Notably, this occurs without HMW complexation and despite the reduced hydrophobicity of RCM α-LA ( Figure 2). In vivo, β-CN associated with the other caseins (of which there are three in bovine milk) to form the large amorphous aggregate known as the casein micelle [22][23][24]. Consistent with their intrinsically disordered nature, β-CN and the other caseins adopt a significant proportion of polyproline-II (PP-II) helical secondary structure, mostly within their proline, glutamine-rich regions [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it has been demonstrated that other regions of sHSPs can also interact with the ACD, including NTD-β4/β8 groove interactions observed in a crystal structure of HSPB6 (69) and NTD-ACD dimer interface contacts as seen in a crystal structure of the HSPB2-HSPB3 hetero-tetramer (70). The CTRs of sHSPs play key roles in promoting solubility and contributing to the regulation of interactions with other proteins (71,72), similar to the roles of other intrinsically disordered regions (73). In addition, the CTR of HSPB2 was shown to regulate its ability to undergo liquid-liquid phase separation (74).…”
Section: Discussionmentioning
confidence: 99%